THE USE OF Q-METHODOLOGY IN EXPLORING FARMERS’ PERSPECTIVES IN THE CONTEXT OF CLIMATE CHANGE - Desptović, Jelena; Vukelić, Nataša; Šarac, Veljko; Rodić, Vesna (Journal of Agricultural Sciences (Belgrade), 2025)
This paper aimed to scope the literature to examine the extent to which Q-methodology has been employed in empirical studies in order to measure farmers’ perspectives in various contexts of climate change. The analysis revealed a surprisingly limited application of Q-methodology in this area. A search of the SCOPUS database, using the advanced search string TITLE-ABS-KEY (“Q-method*” OR “Q-sort*” OR “Q-stud*” OR “Q-technique” AND “farmer*” OR “agricultur*” AND “clima*”), identified 21 published articles that met the specified criteria. All these papers were published over the last decade, indicating an upward trend in the number of publications over the years. The analysis of these studies demonstrates that Q-methodology can be effectively applied in research aimed at uncovering and comprehending farmers’ perceptions regarding climate change mitigation and adaptation to its risks. Despite its evident potential, this method remains underutilized and merits greater attention from scholars and practitioners. To the best of the authors’ knowledge, a review of this nature has not been conducted previously. Hence, this paper makes a substantial contribution and serves as both an incentive and a valuable starting point for researchers contemplating the use of Q-methodology in empirical studies concerning farmers’ subjectivity in the context of climate change.